Right to Hospital Care and Prioritisation from a Law and Politics Perspective – The Experiences of Norway and Denmark. Issue 4 (December 2015) - Aasen, Henriette Sinding; Hartlev, Mette; Magnussen, Anne-Mette
As members of the Nordic family of welfare states, both Norway and Denmark are characterised by universal access to health care. Legislation and individual rights have increasingly been used as tools to promote and protect patients' equal access to health care services. At the same time both countries are struggling with increasing health care expenditures, waiting lists and a demand to prioritise health care resources in light of new and expensive treatment options. This calls for political space to adjust prioritisation policies and procedures. The article analyses the regulation of access to hospital care in Norway and Denmark, from a law and politics perspective. We explore similarities and differences between the two countries with respect to the objectives of the regulation and formulation of the right to hospital care, and how the interplay between law and politics – and juridification and politicisation – is expressed and managed in the regulation. We conclude that even though there are differences between the two countries in the extent of juridification, the regulation in both countries still leaves room for continued political governance of issues related to the prior itisation of health care services.